(untitled) (Linguostylistic Studies, 2021)
Modern linguists do extensive research on the functioning of religious vocabulary during the Soviet period, but the material of Western Ukrainian newspaper speech of this time has not yet been the object of linguistic study. It determines the relevance of this study. Its purose is to reveal the specifics of the preservation and development of the semantics of religious lexemes in the media of nationalists in Western Ukraine during World War II against the background of their lost-of-meaning in the Soviet newspapers of that time. As a result of the analysis of the printed Western Ukrainian mass media of 1939–1945 (Ostanni visti, Volia Pokuttia, Vilne Slovo, Holos Pidkarpattia, Ukrainski visti, Rohatyтske slovo, Samostiina Ukraina, Stanislavske slovo, Chervonyi prapor), the author concludes, that the publications of the Organization of Ukrainian Nationalists consistently propagated sacred vocabulary in the articles, even on non-religious subjects (often to reproduce the elation and triumph of what was being said). Textual syntagmatics of biblical-phraseological level unfolded both in familiar biblical situations (often through the introduction of colloquial elements in publicist speech, such as exclamatory units with religious components), and metaphors which retained the sacral dimension of the original semantics. A specific feature of the functioning of the religious lexicon in this newspaper material was the departure of religious lexemes beyond the traditional usage in the process of shaping ironic-satirical periphrastic units with their participation (червоний / большевицький / інтернаціональний рай ‒ the red/ Bolshevik/international paradise; червоне царство сатани ‒ the red kingdom of Satan; Сталінове “царство” / царство темряви, гніту і голоду ‒ the Stalin “kingdom” / the kingdom of darkness, oppression and hunger). The editorial policy of Krasnoye Znamya, the Soviet-era press organ, was aimed at avoiding religious themes, apparently without any political-ideological guidelines for this in the years 1939-1945. Only in the spring issue of 1945, this newspaper published a totally biased and lengthy article “With a cross or with a knife?” by V. Rossovych (Iaroslav Halan), targeting the Vatican, the Greek Catholic Church and Andrei Sheptytskyi. Sensitive metaphors and metonymies, epithets and hyperboles, phraseology and neologisms, which included religious vocabulary (релігійний лубок ‒ religious bast, боги свастики і тризуба ‒ gods of swastika and trident, ультракатолицька шляхта ‒ ultra-Catholic szlachta, etc.), the extraction of words reserved for the religious sphere with the “weathering” of their semantics (вірник ‒ believer → neologism довірник), biblical allusions, religious words in inverted commas as markers of irony were deployed to fulfill an order of defamation of Andrei Sheptytskyi and Catholicism altogether.